Forecasting the Consumer Confidence Index for Economic Conditions Prediction in Ambon, Indonesia - Albertus Eka Putra Haryanto; Destri Susilaningrum; Indra Nur Fauzi (IPTEK The Journal of Engineering, 2023)
Economic developments in Maluku Province show positive growth. However, this is not accompanied by an increase in the confidence index from consumers. It was recorded that from July to September 2022, there was a decrease in the Consumer Confidence Index of around 7.6% to 8.2%. The value of the Consumer Confidence Index can be forecasted using time series analysis. Time series analysis is a method intended to make an estimation and forecasting for the future. Some methods that can be used in forecasting in this study are naive, moving average, single exponential smoothing, double exponential smoothing, and time series regression. This method can be used to forecast the value of the Consumer Confidence Index in Ambon City after the Covid-19 pandemic. It can be concluded from the analysis results that the best model for forecasting the condition of the consumer confidence index value is the Double Exponential Smoothing method with a combination of Alpha = 0,4 and Gamma = 0,5, The forecast results showed a decrease in the value of the consumer confidence index, although the index still showed a relatively optimistic value.